PETA KEMAMPUAN GURU IPA DALAM MENGEMBANGKAN PENELITIAN TINDAKAN KELAS - Ading Mulyadi (Journal Of Regional Public Administration (JRPA), 2016)
This research purpose is to map teachers understanding on class action research concept. This research is qualitative descriptive study towards a group that had conducted a program. This group has been trained to develop class action research for three years through BERMUTU program in teachers’ group activities (MGMP). Data gained from observation and interview then processed and reduced to identify the important information. The result was compared with expert opinion to seek its similarity and deviation resulted the conclusion of class action research concept and its quality. It shows that teachers’ understanding was varied towards class action research concept. Teachers should do class action research  intentionally and it should improve teaching learning process while they did not conduct their research with this definition. It is also found out that class action research could not give improvement on teachers’ developing theoritical competence yet, since this competence is very important to support teaching learning process. Thus, teachers’ understanding influences the quality of their research report.